ANALISIS GOOGLE SCHOLAR DAN HAKI DALAM MENGHADAPI REVOLUSI INDUSTRI 4.0 MENUJU UNIVERSITAS KELAS DUNIA - Widiyanto, Rohmat; Latip, Asep Ediana; Suryaningsih, Tri; Uswatun, Din Azwar (Elementar : Jurnal Pendidikan Dasar, 2024)
This research aims to identify and develop data on lecturers who have published data and home indexing on the Google Scholar Index and intellectual records at the Director General of Information and Communication Technology; utilizing the google scholar home index citation database and online intellectual property center; Indexing of lecturers' works in the Google Scholar home and obtaining Intellectual Property Rights. This research method is research and development according to Brog & Gall (1989) in Lyesmaya (2015:15) in the implementation of research and development there are several methods used, namely descriptive, evaluative, and experimental methods. The research results are; 1) Implementation of the home scholar Index in the PGMI study program reaches 75%, 2) Intellectual property rights for online lecturers and patents to protect their work, 3) and publication of research results in international journals, and 4) Intellectual Property Rights. The results of this study recognize the achievement of goals in university milestones to support World Class University in the 4.0 era, the Madrasah Ibtidaiyah Teacher Education Study Program (PGMI) personally by lecturers is able to encourage the realization of World Class University in the publishing aspect in the world wide system, the Google Scholar Index of 93.3%, then author Sinta ID by 66.7% and finally the utilization of broadcasting Intellectual Property Rights by 86.7%.